Anggaru Klawu: Metafora Fauna Endemik Indonesia Owa Jawa Dalam Penciptaan Busana Dengan Art Of Beat Style - Mitariani -; I Nyoman Artayasa; Nyoman Dewi Pebryani (Institut Seni Indonesia Padangpanjang, 2021)
Indonesia is a country which has a diversity of flora and fauna. One of the endemic faunas of Indonesia is the Javan Gibbon. The Javan Gibbon (Hylobates Moloch) is a species of small ape without a tail with long arms, gray hair, and a distinctive voice. The Javan gibbon is an animal that is startining become endangered animal and almost extinct so that the IUCN Redlist has categorized as an